An Analysis of Students’ Needs in Developing English Textbooks to Improve High Abilities Level of Law Students - Yosi Marita; Safnil; Syukri Hamzah; Irwan Koto (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2023)
Textbooks are a set of learning materials that are arranged systematically and include competencies that will be mastered by students in learning activities. The presence of textbooks is a crucial element in the teaching and learning process, as they serve as a valuable resource for both students and educators at all levels of education. This research aims to analyze the students’ needs in developing English textbooks to improve high abilities level of law students. This type of research used descriptive qualitative. The research method is a survey through interviews, questionnaires, and documentation, for this reason, a needs analysis questionnaire was given to 56 students to obtain information about their needs in English at the Faculty of Law of Universitas Prof.Dr. Hazairin SH. The results of the data analysis reveal the importance of English textbooks, specifically in the field of Law (English for Specific Purposes). In this case, language skills and reading were more emphasized. Thus, it is concluded that based on the results of the Analysis of textbooks for lecturers, there is a very high need for books with unique characteristics as teaching materials that are suitable for learning English for academic purposes for the Faculty of Law in accordance with ESP principles.